Segregation, choice based letting and social housing: How housing policy can affect the segregation process - Maarten van Ham; David Manley (Institute for the Study of Labor (IZA), 2012)
In this chapter we investigate the process of ethnic minority segregation in English social housing. Successive governments have expressed a commitment to the contradictory aims of providing greater choice - through the introduction of choice based letting - for households accessing an increasingly marginalised social housing sector whilst also expressing a determination to create more mixed communities and neighbourhoods. We consider the concept of choice in the context of a heavily residualised social housing sector, arguing that, for social housing tenants at least, the concept of real choice is a misnomer. We draw on research that has utilised unique administrative data and analysed the moves of all entrants into and movers within the social renting sector over a ten year period in England. The conclusion is that the introduction of choice based letting has influenced the residential outcomes of ethnic minorities and resulted in highly structured neighbourhood sorting that has segregated minority populations into the least desirable neighbourhoods of English cities.
urn:nbn:de:101:1-201206146479
Keywords: R21; R23; 330; segregation; choice based letting; social housing; housing policy; UK; Ethnische Gruppe; Segregation; Sozialer Wohnungsbau; Wohnstandortwahl; Großbritannien